If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10y = 2(3 + y) -10y = (3 * 2 + y * 2) -10y = (6 + 2y) Solving -10y = 6 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -10y + -2y = 6 + 2y + -2y Combine like terms: -10y + -2y = -12y -12y = 6 + 2y + -2y Combine like terms: 2y + -2y = 0 -12y = 6 + 0 -12y = 6 Divide each side by '-12'. y = -0.5 Simplifying y = -0.5
| 0.33X+5+0.25X=X | | 13m=12m+14 | | 3x-(2x-1)=5x+2(3x-4) | | 3x+5x=4+18 | | 1.66X=0.25X+5 | | M^2-12m-57=0 | | 20x+3y=15 | | 6=-2m-7 | | 8x+4=19+6x | | 2/8=12/x | | 2x-20=3(x-15) | | 25/W=20/16 | | 13x^2+11=50 | | .12x+0.2(x-5)=0.01(5x-4) | | Ln(6x-9)+ln(4)=ln(12)+2 | | F(x)=6x^2+1 | | q/22=5/11 | | h=16t^2+40t+6 | | 26-x=34-3x | | 1/25=y/1250 | | 2u-2.3=4.1 | | 2(x+2)-8=12 | | 8/3=t/12 | | 5n^2+8=0 | | -7y+22.9=5.4 | | 14p-21q= | | 7x+9=6x+-5 | | 9x(7+8)= | | 5m^2+5m-30=0 | | 2x+4y+5z=8 | | 3x-6.2=3.4 | | [x-2]=14 |